2021
DOI: 10.1007/s11307-021-01596-y
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme B PET Imaging of Combined Chemotherapy and Immune Checkpoint Inhibitor Therapy in Colon Cancer

Abstract: Purpose Chemotherapeutic adjuvants, such as oxaliplatin (OXA) and 5-fluorouracil (5-FU), that enhance the immune system, are being assessed as strategies to improve durable response rates when used in combination with immune checkpoint inhibitor (ICI) monotherapy in cancer patients. In this study, we explored granzyme B (GZB), released by tumor-associated immune cells, as a PET imaging-based stratification marker for successful combination therapy using a fluorine-18 (18F)-labelled GZB peptide ([… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 32 publications
1
40
0
Order By: Relevance
“…Granzyme B is a major cytotoxic protein that drives cytotoxic T-cell-mediated tumor cell killing [37]. Granzyme B expression in post-therapy tumors has been associated with the immune therapy response in cancer [40][41][42][43]. In the anti-PD-1-sensitive CT26 murine colorectal carcinoma cell line model, granzyme B expression was upregulated 10 days after treatment and was predictive of the response [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Granzyme B is a major cytotoxic protein that drives cytotoxic T-cell-mediated tumor cell killing [37]. Granzyme B expression in post-therapy tumors has been associated with the immune therapy response in cancer [40][41][42][43]. In the anti-PD-1-sensitive CT26 murine colorectal carcinoma cell line model, granzyme B expression was upregulated 10 days after treatment and was predictive of the response [40].…”
Section: Discussionmentioning
confidence: 99%
“…Granzyme B is a serine protease that mediates CD8+ T-cell cytotoxicity [37]. Its expression in cytotoxic lymphocytes is considered a marker of immune activation [38,39] and predicts the immune therapy response in cancer patients [40][41][42][43]. Therefore, we analyzed granzyme B expression in CD8+ cells using tumor samples.…”
Section: Egcg Inhibits Jak/stat Signaling In Tumors and Increases Granzyme Expression In Cd8+ Cells In The B16f10 Tumor Microenvironmentmentioning
confidence: 99%
“…In particular, in vivo imaging approaches with activatable probes utilizing GzmBcleavable IEPD or IEFD linker allow to directly report functional readouts of immune cell (e.g. CTLs and NK cells) infiltration, activation, and cytotoxicity in tumors after immunotherapy treatments (138)(139)(140)(143)(144)(145)(146). Advanced protease-responsive technologies would enable more comprehensive exploration of proteolytic networks in cancer and provide the next generation of clinical modalities for cancer chemotherapy and immunotherapy.…”
Section: Targeting Serine Proteases In Tumor Stromamentioning
confidence: 99%
“…54 Goggi et al have also suggested that GZMB PET imaging of combined chemotherapy and immune checkpoint inhibitor therapy in colon cancer is an accurate biomarker for treatment response. 55 Moreover, Pearson et al found that the expression of GZMB increased the sensitivity of anaplastic large-cell lymphoma to apoptosis induced by staurosporine or doxorubicin. This finding suggests that GZMB expression may be considered a factor leading to a favourable response of lymphoma to treatment.…”
Section: Gzmb and Elimination Of Viruses Or Virus-infected Cellsmentioning
confidence: 99%